2020
DOI: 10.1002/pld3.229
|View full text |Cite
|
Sign up to set email alerts
|

WHIRLY2 plays a key role in mitochondria morphology, dynamics, and functionality in Arabidopsis thaliana

Abstract: WHIRLY2 is a single‐stranded DNA binding protein associated with mitochondrial nucleoids. In the why 2‐1 mutant of Arabidopsis thaliana, a major proportion of leaf mitochondria has an aberrant structure characterized by disorganized nucleoids, reduced abundance of cristae, and a low matrix density despite the fact that the macroscopic phenotype during vegetative growth is not different from wild type. These features coincide with an impairment of the functionality and dynamics of mitochondria that have been ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…During seed germination, normal mitochondrial biogenesis and mtDNA copy number are tightly controlled (Paszkiewicz et al, 2017). This connection between seed germination and mitochondrial defects was also reported in many other studies (Han et al, 2010; Virdi et al, 2015; Van Aken et al, 2016; Heidorn-Czarna et al, 2018; Golin et al, 2020). We showed that variation in root lengths at 5 DAS was heritable among different msh1 mutant families.…”
Section: Discussionsupporting
confidence: 86%
“…During seed germination, normal mitochondrial biogenesis and mtDNA copy number are tightly controlled (Paszkiewicz et al, 2017). This connection between seed germination and mitochondrial defects was also reported in many other studies (Han et al, 2010; Virdi et al, 2015; Van Aken et al, 2016; Heidorn-Czarna et al, 2018; Golin et al, 2020). We showed that variation in root lengths at 5 DAS was heritable among different msh1 mutant families.…”
Section: Discussionsupporting
confidence: 86%
“…While the algae and Marchantia have only one WHIRLY-like protein, higher plant species have at least two WHIRLY proteins. Both have an organelle targeting peptide at the N-terminus, directing them either to mitochondria, plastids, or both organelles ( Krause et al, 2005 ; Golin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…PPRs are RNA‐binding proteins and are found in complexes of organellar mRNA‐editing machineries in plants, which play roles in photosynthesis and respiration, as well as plant development and environmental responses (Barkan and Small, 2014). On the other hand, WHY3 is a member of the three‐gene WHIRLY family of single‐stranded DNA‐binding proteins in Arabidopsis (Cappadocia et al., 2013) and is believed to localize dually in the nucleus or in plastids and mitochondria (Golin et al., 2020; Jiang et al., 2017; Marechal et al., 2009). Its closest homolog WHY1 represses the senescence marker gene WRKY53 and coordinates leaf senescence in a developmental stage‐dependent manner (Huang et al., 2017, 2018; Lin et al., 2019; Miao et al., 2013; Ren et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The WHIRLY family includes the well‐known leaf senescence regulator WHY1 (Miao et al., 2013), the closest paralog of WHY3 . Although WHY3 was recently reported to be involved in protein trafficking between organelles in response to stress (Golin et al., 2020), the detailed role in connection with miR840 is poorly known.…”
Section: Introductionmentioning
confidence: 99%